Building Long-term Resilience - Nayak, Swati; Habib, Muhammad Ashraful; Hossain, Sk Mosharaf (International Rice Research Institute, 2025)
The SDMF pilot was implemented in eight villages across four drought-prone districts of Odisha—Balangir, Kalahandi, Mayurbhanj, and Koraput—to enhance drought resilience, farm income, and seed system sustainability. The project integrated drought-tolerant and aerobic rice varieties, mechanized Direct Seeded Rice (DSR), crop diversification into millets, pulses, and sweet corn, community-based seed systems, and strong institutional convergence, with active participation of women and youth. Improved rice varieties (BRRI Dhan75, BRRI Dhan69, Swarna Shreya, Swarna Samriddhi) recorded yield gains of 1.0–2.25 t/ha over local checks, while mechanized DSR reduced cultivation costs by ₹3,920–4,420 per acre. Crop diversification and fallow land utilization generated significant additional income, particularly from pulses. Seed system strengthening through farmer training and community-managed plots enhanced local seed availability. Women’s engagement in seed production, nutrition gardens, and poultry enterprises improved income and dietary diversity. The pilot demonstrates a scalable, climate-resilient model for drought-affected regions.